Polyphenol acrylamide compound grafted polyurethane, antifouling coating and preparation method
Patent Information
- Application Number
- CN202311455488.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-03
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-11-03
AI Technical Summary
但多酚丙烯酰胺化合物在聚氨酯中的直接添加,容易造成防污剂的释放速率不稳定、可控;物理共混防污剂型涂层材料在水下浸泡后,容易出现局部暴释的现象,影响涂层的防污效果
1、本发明中,基于多酚丙烯酰胺化合物的微相分离聚氨酯防污涂层合成条件简单、可控性好;通过引入多酚丙烯酰胺化合物,提高了材料的机械性能,本发明的涂层拉伸强度可到10 MPa以上,伸长率可到260%以上。
Smart Images

Figure CN117402314B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of marine antifouling technology, specifically to a polyphenol acrylamide compound grafted polyurethane, an antifouling coating, and a preparation method thereof. Background Technology
[0002] Marine biofouling refers to the attachment, growth, and reproduction of marine animals, plants, and microorganisms on the surface of marine facilities, causing significant damage. Marine biofouling not only reduces ship speed, increases fuel consumption, and raises emissions of sulfur oxides and nitrogen oxides, resulting in substantial economic losses and environmental pollution; it also damages paint films, exacerbates corrosion of marine facilities, and increases the risk of equipment damage and accidents.
[0003] Currently, marine antifouling coatings are generally classified as fouling-removing type and self-polishing type. They primarily consist of added metal ions (copper, zinc, silver, etc.) or toxic bactericides. Different antifouling coatings can be prepared depending on the content and form of addition. These coatings prevent marine organisms from adhering to their surfaces by releasing toxic substances and bactericides into the ocean. For example, patent number CN110358396B discloses a long-lasting controlled-release marine antifouling coating and its preparation method, which incorporates a controlled-release antifouling agent into fluorinated acrylic resin and epoxy resin to significantly extend the antifouling durability and improve the utilization rate of the antifouling coating. Patent number CN214299906U discloses a marine antifouling coating and its preparation method, consisting of a three-dimensional network of erosive films and antifouling agents filled within the erosive films. The coating effectively prevents the formation of biofilms in the initial non-destructive stage by releasing sufficient concentrations of copper, silver, and other ions. However, the release of metal ions and antifouling agents into the marine environment not only has harmful effects on non-target marine organisms, but also induces drug resistance in fouling organisms. At the same time, the release rate of antifouling agents added by physical blending is difficult to control, resulting in low stability, durability and effective antifouling properties of the coating.
[0004] Polyurethane coatings are widely used in the automotive, marine, and aerospace industries due to their excellent adhesion, weather resistance, durability, and ease of processing. Therefore, combining polyphenolic acrylamide compounds with antifouling properties with polyurethane coatings not only imparts excellent antifouling performance but also enhances the mechanical properties, making them suitable for harsher environments. However, the direct addition of polyphenolic acrylamide compounds to polyurethane can easily lead to unstable and uncontrollable release rates of the antifouling agent; physically blended antifouling agent coatings are prone to localized burst release after underwater immersion, affecting the coating's antifouling effectiveness.
[0005] Therefore, designing a polyphenol acrylamide-grafted polyurethane antifouling coating by chemically grafting polyphenol acrylamide compounds into the polyurethane structure is of great significance for enhancing the durability and stability of the antifouling coating. However, how to achieve the polymerization of polyphenol acrylamide compounds with polyurethane has not yet been reported. Summary of the Invention
[0006] The purpose of this invention is to at least solve one of the technical problems existing in the prior art, and to design and synthesize a polyphenol acrylamide compound grafted polyurethane with controllable polymerization properties, an antifouling coating, and a preparation method thereof.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a polyphenol acrylamide compound-grafted polyurethane antifouling coating, the structural formula of which is shown below:
[0008] It is composed of the following raw materials in parts by weight: 100-105 parts polyurethane prepolymer, 30-34 parts polyphenol acrylamide compound grafted polyurethane polyol, and 1-1.5 parts defoamer.
[0009] Furthermore, R1 is H or OH; R2 is H or OH, n is a natural number greater than zero, and R1 and R2 can be the same or different.
[0010] Furthermore, the polyphenol acrylamide compound grafted polyurethane polyol is composed of raw materials in the following molar ratio, including 1-2 parts of polyphenol acrylamide compound monomer, 2-5 parts of ether monomer containing double bonds and hydroxyl groups, and 4-5 parts of solvent and 0.01-0.02 parts of initiator added according to the mass ratio of the polyphenol acrylamide compound monomer.
[0011] Furthermore, ether monomers containing double bonds and hydroxyl groups include one or more of ethylene glycol vinyl ethers and 4-terminated hydroxyl vinyl ethers.
[0012] Furthermore, the solvent is dimethylformamide; the initiator is azobisisobutyronitrile.
[0013] A method for preparing a polyphenol acrylamide compound-grafted polyurethane antifouling coating is as follows: a primer is coated onto the surface of a substrate and dried; then, the aforementioned polyphenol acrylamide compound-grafted polyurethane is coated onto the dried primer surface; after curing, a polyphenol acrylamide compound-grafted polyurethane antifouling coating is obtained. Furthermore, the preparation of polyphenol acrylamide compound-grafted polyurethane includes... S1. Pretreatment of polyphenol acrylamide monomers The polyphenol acrylamide monomer is ground and sieved to obtain a polyphenol acrylamide monomer with a smaller particle size; the polyphenol acrylamide monomer is mixed with an appropriate amount of solvent and then placed in an ultrasonic vibrator for ultrasonic vibration for 10-20 minutes to obtain a polyphenol acrylamide monomer solution. S2. Synthesis of polyphenol acrylamide compounds grafted onto polyurethane polyols The polyphenol acrylamide monomer solution of S1 was added to a three-necked flask and mechanically stirred while heating to 90-120°C. Then, the ether monomer containing double bonds and hydroxyl groups and the initiator were added to the three-necked flask and mechanically stirred until homogeneous. The reaction temperature was controlled at 90-120°C, and the reaction was continued for 3-6 hours before heating was stopped. The mixture was then cooled to room temperature to obtain polyphenol acrylamide-grafted polyurethane polyol. The structural formula of the polyphenol acrylamide compound grafted with polyurethane polyol is as follows:
[0014] Wherein, R1 is H or OH; R2 is H or OH, and R1 and R2 can be the same or different.
[0015] S3. Synthesis of polyphenol acrylamide compound grafted polyurethane antifouling coating The polyphenol acrylamide compound grafted polyurethane polyol obtained in step S2 is mixed and stirred with the pre-prepared polyurethane prepolymer and defoamer, and vacuum defoamed until no foaming occurs, to obtain a polyphenol acrylamide compound grafted polyurethane antifouling coating.
[0016] Furthermore, it also includes the synthesis of polyphenol acrylamide compound monomers. The polyphenol compound and N-hydroxymethylacrylamide were added to a three-necked flask containing an appropriate amount of organic solvent and ultrasonically mixed. The mixture was then mechanically stirred at 25-50°C, and 20-80 mL of concentrated sulfuric acid was added dropwise using a constant pressure separatory funnel until a white or light pink precipitate appeared. The precipitate was then filtered and washed multiple times until neutral, then recrystallized and purified, and finally dried to obtain the polyphenol acrylamide compound monomer.
[0017] The structural formula of the polyphenol acrylamide compound monomer is:
[0018] Wherein, R1 is H or OH; R2 is H or OH, and R1 and R2 can be the same or different.
[0019] Furthermore, the mass ratio of polyphenolic compound, N-hydroxymethylacrylamide, organic solvent and concentrated sulfuric acid is 1:2.9~3.2:8~10:1.1~1.5.
[0020] Furthermore, the polyphenolic compound is pyrogallol; the organic solvent is an ethanol solution.
[0021] According to another preferred embodiment of the present invention, the construction method of the prepared antifouling coating is as follows: a primer is applied to the surface of the substrate and dried, and then a modified polyurethane system is applied to the dried primer surface. After curing, a polyphenol acrylamide compound mechanism polyurethane antifouling coating is obtained.
[0022] In this invention, a polyurethane antifouling coating based on a polyphenolic acrylamide compound was prepared using commercial polyurethane component A as a prepolymer and polyphenolic acrylamide compound and ethylene glycol ethylene ether as polyols. The polyphenolic acrylamide compound imparts excellent antifouling properties to the coating. The hydroxyl, amide, and isocyanate groups in the polyphenolic acrylamide compound and the polyurethane provide abundant hydrogen bonds for the coating, giving the material good mechanical strength and adhesion.
[0023] In this invention, the urea group and hydroxyl group work together to form a large number of hydrogen bonds, giving the material excellent mechanical properties. The interaction between the hydroxyl group and the substrate can also improve adhesion. The antifouling agent polyphenol acrylamide compound is introduced into the main chain through covalent bonding to continuously exert its antifouling ability.
[0024] This invention modifies a polyurethane coating by introducing a polyphenolic acrylamide compound into the main chain, thereby improving the static antifouling ability of the polyurethane coating through the antifouling effect of the polyphenolic acrylamide compound. This invention uses pyrogallol, which has a high phenolic hydroxyl content and stable chemical properties, to synthesize the polyphenolic acrylamide compound, and prepares a polyurethane antifouling coating with a polyphenolic acrylamide compound in the main chain through chemical grafting.
[0025] As can be seen from the above description of the present invention, compared with the prior art, the present invention has the following beneficial effects: 1. In this invention, the synthesis conditions of the microphase separation polyurethane antifouling coating based on polyphenol acrylamide compound are simple and controllable; by introducing polyphenol acrylamide compound, the mechanical properties of the material are improved. The tensile strength of the coating of this invention can reach more than 10 MPa and the elongation can reach more than 260%.
[0026] 2. The polyphenolic acrylamide compound in this invention endows the material with antifouling properties and antibacterial ability of over 95% (Escherichia coli: 91%, Staphylococcus aureus: 95%).
[0027] 3. The system is rich in hydroxyl, amide and isocyanate groups, which provide a large number of hydrogen bonds, together giving the coating and the material adhesion.
[0028] 4. The coating design concept is feasible, easy to operate, repeatable, and has the potential for mass production, which can serve as a reference for the research and development of other marine antifouling coatings. Attached Figure Description
[0029] Figure 1 This is a schematic diagram of the polyphenol acrylamide compound grafted polyurethane coating structure in a preferred embodiment of the present invention; Figure 2 This is an infrared spectrum analysis diagram of the polyphenol acrylamide compound in a preferred embodiment of the present invention; Figure 3 , 4 This diagram illustrates the antibacterial properties of a polyphenol acrylamide compound-grafted polyurethane antifouling coating with microphase separation, as described in an embodiment of the present invention. Detailed Implementation
[0030] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0031] Example 1
[0032] A polyphenol-acrylamide compound-grafted polyurethane antifouling coating and its preparation method are disclosed below: S1. Preparation of polyphenol acrylamide monomers 60 g of pyrogallol, 180 g of N,N-hydroxymethylacrylamide, and 600 mL of ethanol were added to a three-necked flask equipped with a mechanical stirrer. The mixture was ultrasonically agitated for 20 min until completely dissolved. The mixture was then stirred in an oil bath at 35 °C. During the reaction, 30 mL of sulfuric acid was slowly added dropwise through a constant-pressure dropping funnel as an acid catalyst. The reaction was continued at 35 °C for 3 days to obtain a polyphenolic acrylamide compound. The product was then washed with deionized water and filtered until neutral. Finally, it was purified by recrystallization from ethanol to obtain a polyphenolic acrylamide compound. The polyphenolic acrylamide monomer was ground, sieved, mixed with an appropriate amount of solvent, and ultrasonically agitated for 10–20 min to obtain the polyphenolic acrylamide compound.
[0033] S2. Synthesis of polyphenol acrylamide compounds grafted with polyols 10 g of polyphenol acrylamide compound, 6.45 mL of ethylene glycol ethylene ether, and 90 mL of dimethylformamide were added to a three-necked flask equipped with a mechanical stirrer. The mixture was heated in an oil bath at 100 °C and stirred until completely dissolved. Then, 0.05 g of azobisisobutyronitrile was slowly added as an initiator. The mixture was reacted continuously at 100 °C and 230 rpm for 3 h. After cooling to room temperature, the polyphenol acrylamide compound grafted polyol was obtained.
[0034] S3. Synthesis of polyphenol acrylamide compound grafted polyurethane antifouling coating 10 g of polyphenol acrylamide-grafted polyol, 23 g of commercial polyether polyurethane component A, and 0.33 g of defoamer were added to a beaker and mechanically stirred until uniformly mixed. The mixture was then placed in a vacuum oven for vacuum defoaming for 5 min. The product was then transferred to a mold and vacuum defoamed again for 20 min. After defoaming was completed, the mixture was cured at room temperature for 3 days to obtain a polyphenol acrylamide-grafted polyurethane antifouling coating, which was named PUA-10.
[0035] The obtained product was identified as the polyphenol acrylamide compound by conventional infrared spectroscopy analysis, and the results are shown in the appendix. Figure 2 3437 cm -1 The peak represents the stretching vibration of the OH hydroxyl group; 3232 cm⁻¹ -1 The stretching vibration peak of NH; 3074 cm⁻¹ -1 The peak at 1650 cm⁻¹ represents the bending vibration of C=CH; the peak at 1598 cm⁻¹ represents the stretching vibration of the carbonyl group C=O; -1 1533 cm -1 Characteristic peak of benzene ring; 1248 cm⁻¹ -1 This is the CO stretching vibration peak of the phenolic hydroxyl group; 717 cm⁻¹ -1 The peak at that position also confirms the presence of ortho-trisubstituted benzene rings. These findings indicate the successful synthesis of the polyphenolic acrylamide compound.
[0036] Tensile performance tests on the above-mentioned antifouling coatings showed that PUA-10% had higher tensile strength and elongation than commercial polyurethane coatings, with an elongation at break of up to 224% and a tensile strength of up to 9.73 MPa. This is attributed to the increased crosslinking density in the system as the polyphenol acrylamide compound polyol content increases, and the phenolic hydroxyl and amide groups in the polyphenol can enrich the hydrogen bonds in the system, thus improving the mechanical properties of the coating.
[0037] To investigate the degree of microphase separation in the coating, AFM atomic force microscopy was performed on the antifouling coating, and the roughness was compared after 7 days and 30 days. For PUA-10%, the roughness characterization parameters Rq were 2.97 and Ra were 1.47 after 7 days, and Rq was 109 and Ra was 75.8 after 30 days, showing a significant increase in roughness. This is due to the microphase separation phenomenon between the polyphenol acrylamide compound and the polyurethane A component, with multiple acrylamide compounds accumulating on the coating surface, thus increasing the surface roughness.
[0038] Example 2 A polyphenol-acrylamide compound-grafted polyurethane antifouling coating and its preparation method are disclosed below: S1. Preparation of polyphenol acrylamide monomers 60 g of pyrogallol, 180 g of N,N-hydroxymethylacrylamide, and 600 mL of ethanol were added to a three-necked flask equipped with a mechanical stirrer. The mixture was ultrasonically agitated for 20 min until completely dissolved. The mixture was then stirred in an oil bath at 35 °C. During the reaction, 30 mL of sulfuric acid was slowly added dropwise through a constant-pressure dropping funnel as an acid catalyst. The reaction was continued at 35 °C for 3 days to obtain a polyphenolic acrylamide compound. The product was then washed with deionized water and filtered until neutral. Finally, it was purified by recrystallization from ethanol to obtain a polyphenolic acrylamide compound. The polyphenolic acrylamide monomer was ground, sieved, mixed with an appropriate amount of solvent, and ultrasonically agitated for 10–20 min to obtain the polyphenolic acrylamide compound.
[0039] S2. Synthesis of polyphenol acrylamide compounds grafted with polyols 10 g of polyphenol acrylamide compound, 6.45 mL of ethylene glycol ethylene ether, and 66.67 mL of dimethylformamide were added to a three-necked flask equipped with a mechanical stirrer. The mixture was heated in an oil bath at 100 °C and stirred until completely dissolved. Then, 0.05 g of azobisisobutyronitrile was slowly added as an initiator. The reaction was carried out continuously at 100 °C and 230 rpm for 3 h. After cooling to room temperature, the polyphenol acrylamide compound grafted polyol was obtained.
[0040] S3. Synthesis of polyphenol acrylamide compound grafted polyurethane antifouling coating 10 g of polyphenol acrylamide-grafted polyol, 23 g of commercial polyether polyurethane component A, and 0.33 g of defoamer were added to a beaker and mechanically stirred until uniformly mixed. The mixture was then placed in a vacuum oven for vacuum defoaming for 5 min. The product was then transferred to a mold and vacuum defoamed again for 20 min. After defoaming, the mixture was cured at room temperature for 3 days to obtain a polyphenol acrylamide-grafted polyurethane antifouling coating, which was named PUA-15.
[0041] Tensile performance tests on the above-mentioned antifouling coatings showed that PUA-15% had higher tensile strength and elongation than commercial polyurethane coatings, with an elongation at break of up to 255% and a tensile strength of up to 11.10 MPa. This is attributed to the increased crosslinking density in the system as the polyphenol acrylamide compound polyol content increases, and the phenolic hydroxyl and amide groups in the polyphenol can enrich the hydrogen bonds in the system, thus improving the mechanical properties of the coating.
[0042] To investigate the degree of microphase separation in the coating, AFM atomic force microscopy was performed on the antifouling coating, and the roughness was compared after 7 days and 30 days. For PUA-15%, the roughness characterization parameters Rq were 3.69 and Ra were 1.82 after 7 days, and Rq was 101 and Ra was 81.2 after 30 days, showing a significant increase in roughness. This is due to the microphase separation phenomenon between the polyphenol acrylamide compound and the polyurethane A component, with multiple acrylamide compounds accumulating on the coating surface, thus increasing the surface roughness.
[0043] Example 3 A polyphenol-acrylamide compound-grafted polyurethane antifouling coating and its preparation method are disclosed below: S1. Preparation of polyphenol acrylamide monomers 60 g of pyrogallol, 180 g of N,N-hydroxymethylacrylamide, and 600 mL of ethanol were added to a three-necked flask equipped with a mechanical stirrer. The mixture was ultrasonically agitated for 20 min until completely dissolved. The mixture was then stirred in an oil bath at 35 °C. During the reaction, 30 mL of sulfuric acid was slowly added dropwise through a constant-pressure dropping funnel as an acid catalyst. The reaction was continued at 35 °C for 3 days to obtain a polyphenolic acrylamide compound. The product was then washed with deionized water and filtered until neutral. Finally, it was purified by recrystallization from ethanol to obtain a polyphenolic acrylamide compound. The polyphenolic acrylamide monomer was ground, sieved, mixed with an appropriate amount of solvent, and ultrasonically agitated for 10–20 min to obtain the polyphenolic acrylamide compound.
[0044] S2. Synthesis of polyphenol acrylamide compounds grafted with polyols 10 g of polyphenol acrylamide compound, 6.45 mL of ethylene glycol ethylene ether, and 40 mL of dimethylformamide were added to a three-necked flask equipped with a mechanical stirrer. The mixture was heated in an oil bath at 100 °C and stirred until completely dissolved. Then, 0.05 g of azobisisobutyronitrile was slowly added as an initiator. The mixture was reacted continuously at 100 °C and 230 rpm for 3 h. After cooling to room temperature, the polyphenol acrylamide compound grafted polyol was obtained.
[0045] S3. Synthesis of polyphenol acrylamide compound grafted polyurethane antifouling coating 10 g of polyphenol acrylamide-grafted polyol, 23 g of commercial polyether polyurethane component A, and 0.33 g of defoamer were added to a beaker and mechanically stirred until uniformly mixed. The mixture was then placed in a vacuum oven for vacuum defoaming for 5 min. The product was then transferred to a mold and vacuum defoamed again for 20 min. After defoaming was completed, the mixture was cured at room temperature for 3 days to obtain a polyphenol acrylamide-grafted polyurethane antifouling coating, which was named PUA-20.
[0046] Tensile performance tests on the above-mentioned antifouling coatings showed that PUA-20% had higher tensile strength and elongation than commercial polyurethane coatings, with an elongation at break of up to 262% and a tensile strength of up to 13.50 MPa. This is attributed to the increased crosslinking density in the system as the polyphenol acrylamide compound polyol content increases, and the phenolic hydroxyl and amide groups in the polyphenol can enrich the hydrogen bonds in the system, thus improving the mechanical properties of the coating.
[0047] To investigate the degree of microphase separation in the coating, AFM atomic force microscopy was performed on the antifouling coating, and the roughness was compared after 7 days and 30 days. For PUA-20%, the roughness characterization parameters Rq were 4.70 and Ra were 2.43 after 7 days, and Rq was 121 and Ra was 96.7 after 30 days, showing a significant increase in roughness. This is due to the microphase separation phenomenon between the polyphenol acrylamide compound and the polyurethane A component, with multiple acrylamide compounds accumulating on the coating surface, thus increasing the surface roughness.
[0048] Example 4 A polyphenol-acrylamide compound-grafted polyurethane antifouling coating and its preparation method are disclosed below: S1. Preparation of polyphenol acrylamide monomers 60 g of pyrogallol, 180 g of N,N-hydroxymethylacrylamide, and 600 mL of ethanol were added to a three-necked flask equipped with a mechanical stirrer. The mixture was ultrasonically agitated for 20 min until completely dissolved. The mixture was then stirred in an oil bath at 35 °C. During the reaction, 30 mL of sulfuric acid was slowly added dropwise through a constant-pressure dropping funnel as an acid catalyst. The reaction was continued at 35 °C for 3 days to obtain a polyphenolic acrylamide compound. The product was then washed with deionized water and filtered until neutral. Finally, it was purified by recrystallization from ethanol to obtain a polyphenolic acrylamide compound. The polyphenolic acrylamide monomer was ground, sieved, mixed with an appropriate amount of solvent, and ultrasonically agitated for 10–20 min to obtain the polyphenolic acrylamide compound.
[0049] S2. Synthesis of polyphenol acrylamide compounds grafted with polyols 10 g of polyphenol acrylamide compound, 6.45 mL of ethylene glycol ethylene ether, and 30 mL of dimethylformamide were added to a three-necked flask equipped with a mechanical stirrer. The mixture was heated in an oil bath at 100 °C and stirred until completely dissolved. Then, 0.05 g of azobisisobutyronitrile was slowly added as an initiator. The mixture was reacted continuously at 100 °C and 230 rpm for 3 h. After cooling to room temperature, the polyphenol acrylamide compound grafted polyol was obtained.
[0050] S3. Synthesis of polyphenol acrylamide compound grafted polyurethane antifouling coating 10 g of polyphenol acrylamide-grafted polyol, 23 g of commercial polyether polyurethane component A, and 0.33 g of defoamer were added to a beaker and mechanically stirred until uniformly mixed. The mixture was then placed in a vacuum oven for vacuum defoaming for 5 min. The product was then transferred to a mold and vacuum defoamed again for 20 min. After defoaming was completed, the mixture was cured at room temperature for 3 days to obtain a polyphenol acrylamide-grafted polyurethane antifouling coating, which was named PUA-25.
[0051] Tensile performance tests on the above antifouling coatings showed that PUA-25% had the highest tensile strength and elongation, with an elongation at break of up to 280% and a tensile strength of up to 15 MPa. This is attributed to the increased crosslinking density in the system as the polyphenol acrylamide compound polyol content increases, and the phenolic hydroxyl and amide groups in the polyphenol can enrich the hydrogen bonds in the system, thus improving the mechanical properties of the coating.
[0052] To investigate the degree of microphase separation in the coating, AFM atomic force microscopy was performed on the antifouling coating. The roughness was compared after 7 days and 30 days. After 7 days, the roughness parameters Rq and Ra for PUA-20% were 5.57 and 3.35, respectively. After 30 days, Rq was 158 and Ra was 124. The addition of the polyphenol acrylamide compound significantly increased the surface roughness of the coating after 30 days. This is due to microphase separation between the polyphenol acrylamide compound and the polyurethane A component, resulting in the accumulation of multiple acrylamide compounds on the coating surface, thus increasing the surface roughness.
[0053] Example 5 The preparation of commercial polyurethane coatings involves the following steps: 10g of polyether polyurethane component B, 23g of commercial polyether polyurethane component A, and 0.33g of defoamer were added to a beaker and mechanically stirred until uniformly mixed. The mixture was then placed in a vacuum oven for vacuum defoaming for 5 minutes. The product was then transferred into a mold and vacuum defoamed again for 20 minutes. After defoaming was completed, the mixture was cured at room temperature for 3 days to obtain a commercial polyurethane coating, named PU.
[0054] Tensile performance tests on the above-mentioned antifouling coatings show that commercial polyurethane coatings have the lowest tensile strength and elongation, with an elongation at break of up to 203% and a tensile strength of up to 8.50 MPa. To investigate the degree of microphase separation in the coating, AFM atomic force microscopy was performed on the antifouling coating, and the roughness was compared after 7 days and 30 days. The commercially available polyurethane coating used for comparison showed relatively small changes in roughness parameters (Rq 2.56, Ra 1.21) after 7 days and (Rq 2.28, Ra 1.39) after 30 days. However, the addition of polyphenolic acrylamide significantly increased the surface roughness of the coating after 30 days, and this increase was further observed with increasing polyphenolic acrylamide content. This is attributed to microphase separation between the polyphenolic acrylamide and polyurethane component A, leading to the accumulation of multiple acrylamide compounds on the coating surface and thus increasing surface roughness.
[0055] Example 6 The antibacterial performance test of the polyphenol acrylamide compound-grafted polyurethane antifouling coating of this invention is carried out through the following steps: (1) Bacterial culture First, prepare a solid culture medium and sterilize it at high temperature. Pour the medium into petri dishes and cool to room temperature before the temperature drops to 70°C. Then, streak the bacteria onto the petri dishes and incubate them at 37°C for 24 hours. Finally, prepare a liquid culture medium and sterilize it at high temperature. After the medium cools to room temperature, remove the streaked bacteria from the previous day, take a small amount and add it to 50 mL of liquid culture medium. Then, incubate the bacterial solution at 37°C for 24 hours.
[0056] (2) Co-culture of bacteria in samples First, prepare samples (1 cm × 1 cm) for each group, with 3 replicates per group. Then, prepare liquid culture medium and sterilize it at high temperature. After the culture medium cools to room temperature, take the corresponding number of test tubes, add 5 mL of liquid culture medium and sample to the test tubes, then add 100 μL of bacterial suspension to the test tubes, and finally place the test tubes in a constant temperature incubator at 37 ℃ for 24 h.
[0057] (3) Antibacterial performance test Remove the sample and place it in a 10 mL centrifuge tube. Soak and shake in deionized water for 2 h to wash away surface bacteria into the solution. Dilute the washing solution 10³ times, then use a pipette to add 100 μL of the solution to LB solid medium. Spread the bacterial solution evenly on the solid medium using a spreader. Then incubate in a 37 ℃ constant temperature incubator for 24 h and observe the number of colonies. The inhibition rate Ea can be calculated by comparing the number of colonies in the test sample with the number of colonies in the blank sample. The specific calculation formula is shown in the formula.
[0058]
[0059] In the formula: Na represents the number of colonies on the culture medium after the blank sample is coated and incubated; Nm represents the number of colonies on the culture medium after the sample is coated and incubated.
[0060] The antibacterial properties of the polyphenol acrylamide-grafted polyurethane antifouling coatings with microphase separation prepared in Examples 1-5 are shown in the graphs. Figure 3 , 4 As shown, the control coating sample exhibited a high density of bacterial adhesion. The polyurethane coating with added acrylamide compounds showed a significant reduction in colony count. This is mainly because the phenolic hydroxyl groups, benzene rings, and amide groups in the polyphenolic acrylamide compounds possess bactericidal properties. However, due to the short storage time of the coating, the surface polyphenolic acrylamide compound content was low, resulting in an antibacterial capacity of only 85%. With increasing storage time, only a small number of colonies were found on the PUA-25% coating after 30 days. The bactericidal rate reached over 99%, and other samples showed the same phenomenon. The results indicate that the PUA-x% coating possesses excellent antibacterial ability based on the bactericidal effect of the polyphenolic acrylamide compounds.
[0061] Experimental results show that the prepared coating not only has the mechanical strength (tensile strength higher than 10 MPa) of polyurethane coating, but also has improved bactericidal ability (the bactericidal rate of Escherichia coli is up to 91%, and the bactericidal rate of Staphylococcus aureus is up to 92%).
[0062] This invention first reacts a polyphenolic acrylamide compound with a double-bonded hydroxyl ether to synthesize a polyurethane polyol (component B), then mixes it with a polyurethane prepolymer (component A), and coats the resulting modified polyurethane onto a substrate surface to obtain a polyphenolic acrylamide-grafted polyurethane antifouling coating. This invention utilizes free radical polymerization to graft polyphenolic acrylamide compounds onto the polyurethane polyol backbone, effectively improving the compatibility and bonding ability between the polyphenolic acrylamide compound and the polyurethane system. Combined with the good adhesion, weather resistance, and durability of the polyurethane matrix itself, and the good antibacterial, antifouling, and environmentally friendly properties of the polyphenolic acrylamide compound, a polyphenolic acrylamide-grafted polyurethane antifouling coating with excellent antifouling properties, durability, and stability is ultimately obtained. In this invention, the amount of functional groups of the polyphenolic acrylamide compound added can reach up to 25 wt%, effectively inhibiting the attachment and growth of marine fouling organisms, extending the service life of the antifouling coating, and providing a new development approach for the preparation of antifouling agent-based polyurethane antifouling coatings.
[0063] To address the above problems, based on previous work and through extensive experimental research, the inventors have finally designed and synthesized a series of polyphenol-acrylamide compound-grafted polyurethane antifouling coatings with controllable polymerization properties. This coating design is feasible, easy to operate, repeatable, and has the potential for mass production, providing valuable insights for the development of other marine antifouling coatings.
[0064] Without causing conflict, those skilled in the art can freely combine and use the above-mentioned additional technical features.
[0065] It is understood that the present invention has been described through some embodiments, and those skilled in the art will recognize that various changes or equivalent substitutions can be made to these features and embodiments without departing from the spirit and scope of the invention. Furthermore, under the teachings of the present invention, these features and embodiments can be modified to adapt to specific situations and materials without departing from the spirit and scope of the invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the protection scope of the present invention.
Claims
1. A polyphenol-acrylamide compound-grafted polyurethane, characterized in that, The polyphenol-acrylamide compound grafted polyurethane has the following structural formula: ; It is composed of the following raw materials in parts by weight: 100-105 parts polyurethane prepolymer, 30-34 parts polyphenol acrylamide compound grafted polyol, and 1-1.5 parts defoamer; R1 is H or OH; R2 is H or OH, R1 and R2 are not both H, and n is a natural number greater than zero.
2. A method for preparing a polyphenol-acrylamide compound-grafted polyurethane antifouling coating, characterized in that, The method is as follows: A primer is applied to the bottom surface of the substrate and dried. Then, the polyphenol acrylamide compound-grafted polyurethane of claim 1 is applied to the dried primer surface. After curing, a polyphenol acrylamide compound-grafted polyurethane antifouling coating is obtained.
3. The method for preparing the polyphenol acrylamide compound-grafted polyurethane antifouling coating according to claim 2, characterized in that: The preparation of the polyphenol acrylamide compound grafted polyurethane includes S1. Pretreatment of polyphenol acrylamide monomers The polyphenol acrylamide monomer is ground and sieved to obtain a polyphenol acrylamide monomer with a smaller particle size; the polyphenol acrylamide monomer is mixed with an appropriate amount of solvent and then placed in an ultrasonic vibrator for ultrasonic vibration for 10-20 minutes to obtain a polyphenol acrylamide monomer solution. S2. Synthesis of polyphenol acrylamide compounds grafted with polyols The polyphenol acrylamide monomer solution of S1 was added to a three-necked flask and mechanically stirred while heating to 90-120°C. Then, the ether monomer containing double bonds and hydroxyl groups and the initiator were added to the three-necked flask and mechanically stirred until homogeneous. The reaction temperature was controlled at 90-120°C, and the reaction was continued for 3-6 hours before heating was stopped. The mixture was then cooled to room temperature to obtain the polyphenol acrylamide grafted polyol. S3. Synthesis of polyphenol acrylamide-grafted polyurethane The polyphenol acrylamide compound grafted polyol obtained in step S2 is mixed and stirred with the pre-prepared polyurethane prepolymer and defoamer, and then vacuum-defoamed until no bubbles are present to obtain polyphenol acrylamide compound grafted polyurethane.
4. The method for preparing the polyphenol acrylamide compound-grafted polyurethane antifouling coating according to claim 3, characterized in that: It also includes the synthesis of polyphenol acrylamide compound monomers. The polyphenol compound and N-hydroxymethylacrylamide were added to a three-necked flask containing an appropriate amount of organic solvent and ultrasonically mixed. The mixture was then mechanically stirred at 25-50°C, and 20-80 mL of concentrated sulfuric acid was added dropwise using a constant pressure separatory funnel until a white or light pink precipitate appeared. The precipitate was then filtered and washed multiple times until neutral, then recrystallized and purified, and finally dried to obtain the polyphenol acrylamide compound monomer.
5. The method for preparing the polyphenol acrylamide compound-grafted polyurethane antifouling coating according to claim 4, characterized in that: The mass ratio of the polyphenol compound, N-hydroxymethylacrylamide, organic solvent and concentrated sulfuric acid is 1:2.9~3.2:8~10:1.1~1.
5.
6. The method for preparing the polyphenol acrylamide compound-grafted polyurethane antifouling coating according to claim 4, characterized in that: The polyphenolic compound is pyrogallol; the organic solvent is ethanol.
Citation Information
Patent Citations
A long-lasting controlled-release marine antifouling coating
CN110358396B